2018
DOI: 10.4028/www.scientific.net/msf.925.118
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Models for Spheroidal Graphite Growth

Abstract: Recent experiments resolved nucleation and growth of graphite during solidification of ductile cast iron in 3D and time using synchrotron X-ray tomography [1]. We use the experimental observations to analyse the relation between graphite growth rate and the state of the particle neighbourhood to pinpoint possible links between growth rate of individual graphite spheres and the overall solidification state. With this insight we revisit existing models for growth of spheroidal graphite and discuss possible modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…X-ray imaging using synchrotron radiation has allowed observation of the solidification behavior in various metallic alloys such as Sn alloys, [7][8][9][10][11][12][13][14][15][16] Al alloys, 9,10,17,18) cast iron, [19][20][21][22][23] Fe-C steels, 11,[24][25][26][27][28] and stainless steels. 29) Installing a deformation device in the observation apparatus, in-situ observation of semisolid deformation by X-ray transmission imaging (referred to as 2D observation hereinafter) was achieved with a high spatial resolution with respect to grain size.…”
Section: Introductionmentioning
confidence: 99%
“…X-ray imaging using synchrotron radiation has allowed observation of the solidification behavior in various metallic alloys such as Sn alloys, [7][8][9][10][11][12][13][14][15][16] Al alloys, 9,10,17,18) cast iron, [19][20][21][22][23] Fe-C steels, 11,[24][25][26][27][28] and stainless steels. 29) Installing a deformation device in the observation apparatus, in-situ observation of semisolid deformation by X-ray transmission imaging (referred to as 2D observation hereinafter) was achieved with a high spatial resolution with respect to grain size.…”
Section: Introductionmentioning
confidence: 99%
“…The final volume of N2 and N3 is overestimated while it is underestimated for N1 and well predicted for N4. This is not a 18 surprise given the individual differences in growth conditions which result in growth rate variations between otherwise similar nodules as discussed by Bjerre et al [34]. The current investigation only considers growth of regular nodules to ensure a relevant experimental basis for comparison to simulated results.…”
Section: Nodule Growthmentioning
confidence: 80%
“…By comparing growth rates of neighbouring nodules and taking into account the arrangement of graphite, austenite and liquid, Boeri et al [34] found that proximity of a nodule to the last-to-solidify regions contribute to high growth rates even during late stages of solidification. Nodules situated among several neighbours exhibited sluggish growth and the overall growth plateaued relatively early.…”
mentioning
confidence: 99%
“…The two graphite particles shown in Figure 1a and g form at approximately the same time, but their shapes and final sizes become significantly different during the course of solidification. The final size of the particles appears to be determined by local variations in carbon concentrations, determined by distance to nearest neighbours and growth of austenite in adjacent regions [15,16]. Graphite particles forming early in solidification are not impinged by their neighbouring particles, and even though they are encapsulated in austenite they grow relatively fast.…”
Section: Resultsmentioning
confidence: 99%